Effects of steam pelleting and extruding sorghum grain-soybean meal diets on phosphorus availability for swine - Trotter, M.; Allee, G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two feeding trials and three phosphorus balance studies were conducted to compare the effect of steam pelleting, extruding, and grinding on phosphorus availability. The results indicate that steam pelleting or extruding has little, if any, effect on the availability of phosphorus for finishing swine (100 to 220 lbs.).
Keywords: Swine; Steam pelleting; Sorghum; Phosphorus